Analisis Strategi Promosi dan Minat Pembeli Properti di BIMURA RESIDENCE - Cholifatur Rizkiya; Waqiatul Aqidah; Ainol Yaqin (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
The purpose of this research is to find out the promotional strategy carried out by Bimura Residence in increasing the interest of buyers. The location of this research was carried out at Bimura Residence which is located in Kampung Baru Hamlet, RT. 15/RW. 4, Binor Village, Paiton. The research method used is descriptive qualitative method to investigate processes and situations. The results of this study indicate that the application of this promotional mix can provide positive benefits to consumer interest in Bimura Residence. The promotional marketing strategy implemented can provide positive benefits to increasing consumer interest in Bimura Residence. That way the existence of the Bimura Residence is better known and cared for by the local community. In the purchasing process there are several supporting factors that influence consumer interest, namely the first is that the service provided is very good, good communication so as to provide comfort to consumers and also a strategic place. These factors can influence consumer interest in subsidized housing at Bimura Residence.